PERANCANGAN VIDEO AGROWISATA SAWAH SOLOK SEBAGAI MEDIA PROMOSI - D.RAVI DERAJAT, DERAJAT; Eliya Pebriyeni (DEKAVE : Jurnal Desain Komunikasi Visual, 2021)
Solok City is one of the cities in West Sumatra Province which is geographically quite unique, that is, this city has various tourist sites. This diversity gives rise to natural exoticism so that it can be used as a tourist attraction. Therefore, as an introduction to tourism in the city of Solok, West Sumatra as well as to advance the tourism sector in the city of Solok, the authors put it in the form of designing a videography-based agro tourism promotion. The research method used qualitative methods with data collection techniques using observation, interviews, and existing. The concept used in the design is "promotion". This means that the concept of Sawah Solok tourism has a beauty and uniqueness in every tourist location. The concept will be applied to each design which includes video and other supporting media. The result of making videos and promotional media for agro tourism is an effort to introduce tourism in Solok City to attract tourists to visit. Besides promoting agro tourism which can be enjoyed in various media. The design produces the main media, namely videos about the natural beauty of Sawah Solok and is also supported by several other supporting media, namely: posters, t-shirts, banners, stickers, mugs, and totte bags as supporting main media and as promotional media.Keywords: Video, Promotion, Agro-tourism, Sawah Solok